Opportunities and Constraints of Promoting New Tree Crops—Lessons Learned from Jatropha - Wouter M. J. Achten (Sustainability, 2014)
It is not uncommon that new crops suddenly attract a lot and international attention from private and public actors based on their acclaimed potential to contribute to sustainable development. Such sharp increases in attention can lead to big investments and promotion campaigns to domesticate and commercialize these crops at industrial scale. However, in many cases the research of these plants is still in its infancy and investors generally lack sufficient insight into uncertainties and risks related to their investments, which consequently hold sustainability risks.